Clinical Value Study on Contrast-Enhanced Ultrasound Combined with Enhanced CT in Early Diagnosis of Primary Hepatic Carcinoma. (2nd September 2022) - Zhang, Libo; Gu, Junyi; Li, Ya; Ren, Zhen; Zhang, Bo; Yu, Zuoren
Abstract : Objective . To explore the clinical value of contrast-enhanced ultrasound combined with enhanced CT in the early diagnosis of primary hepatic carcinoma (PHC). Methods . 84 patients with suspected PHC in the early stage treated in our hospital from January 2020 to January 2022 were selected as the study subjects. All patients underwent contrast-enhanced ultrasound and enhanced CT examinations, and the surgery was performed for resection of lesions within 1 month. According to the results of postoperative pathology diagnosis, the benign group and the malignant group were included. The case data were viewed for the retrospective study to analyze the clinical application value by evaluating the diagnostic efficiency of contrast-enhanced ultrasound, enhanced CT, and their combination for PHC. Results . Among 84 suspected patients, 70 patients had PHC (malignant group) and 14 patients had other hepatic lesions (benign group) after postoperative histopathological examination. There was no significant difference in age, gender, clinical symptoms, and educational level between the two groups (P > 0.05 ), with obvious differences in the history of chronic hepatic disease, smoking, drinking, and infection of hepatitis B virus (HBV) between the two groups (P < 0.05 ). The enhancement time and regression time of the two groups were significantly different (P < 0.05 ), with no statistical difference in the enhancement pattern of photography (P > 0.05 ). For patients with PHC, the imaging features of the two inspection methods at arterial phase and lag phase were statistically different (P < 0.05 ). Taking pathologic findings as the gold standard, the accuracy, sensitivity, specificity, positive predictive value, and negative predictive value of joint diagnosis were significantly higher than those of contrast-enhanced ultrasound and enhanced CT (P < 0.05 ), and the area under the curve of joint diagnosis was obviously larger than that of contrast-enhanced ultrasound and enhanced CT by placing the ROC curve for examination (P < 0.05 ). Conclusion . The combination of contrast-enhanced ultrasound and enhanced CT has a higher accuracy in the early diagnosis of PHC, and the diagnostic efficiency of contrast-enhanced ultrasound is higher than that of enhanced CT. In clinical practice, the physical condition and state of illness in patients should be fully considered, and the most suitable examination method should be selected to reduce their medical burden by taking into account their economic situation.